ANALISIS PENELUSURAN MASKER SEBAGAI PROTOKOL KESEHATAN SAAT PANDEMI COVID-19 DI INDONESIA: STUDI GOOGLE TRENDS - Ully Febra Kusuma; Nurunnisa Arsyad; Melissa Shalimar Lavinia; Selvia Rahayu; Muhammad Khairul Kahfi Pasaribu; Rizma Adlia Syakurah (VISIKES: Jurnal Kesehatan Masyarakat, 2021)
AbstrakMedical masks are also used by people at risk who are indicated to need them. The supply of medical masks is limited, the general public is encouraged to use non-medical masks or cloth masks. This article will discuss the comparison of search results for sensi masks, cloth masks and N-95 masks using google trend analysis. This research method is a qualitative and quantitative study using time series data with quantitative analysis, time-lag correlation is used to assess whether an increase in GT data is correlated with an increase in COVID-19 cases. Data from google trends regarding keywords related to one of the preventive measures for COVID-19, namely masks such as "sensi masks", "cloth masks" and "N-95 masks". Each search interest usually reaches a peak depending on the situation and conditions that occur at that time. The keyword search for "N-95 masks" experienced a peak when 2 Indonesians were confirmed positive for COVID-19, namely on March 2, 2020 and the day after that the keyword "sensi mask" also experienced the highest peak of searches. The keyword search for "cloth masks" peaked on March 6, 2020, when the price of sensi masks began to rise. The results of the keyword correlation test for “sensi mask”, “cloth mask” and “N-95 mask” show that the keyword search results on Google trended a decline in line with the increase in COVID-19 cases in Indonesia. Public interest in tracing increased at the beginning of COVID-19 entering Indonesia. However, the interest in this search continues to decline and is inversely proportional to the increase in the incidence of COVID-19 cases in Indonesia. Keywords:  COVID-19, sensi masks, medical masks, cloth masks, N-95 masks, Google trends